Conservation and economic aspects of a combination of forestry-agricultural crops (Neolamarckia cadamba-Phaseolus vulgaris) and terrace systems in different slope classes - Karyati Karyati; Sri Sarminah; Karmini Karmini; Ali Muhammad Akbar; Rifaldi Hermansyah (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2021)
The utilization of steep lands by planting forestry and agricultural species can provide benefits from soil-water conservation and economic aspects. The combination of planting Neolamarckia cadamba-Phaseolus vulgaris and terrace systems can increase land use values, such as soil conservation, crop production, and farmers’ income. The aim of this study was to analyze silvicultural, hydro-orological, and economic aspects of a combination of forestry-agricultural crops (N. cadamba – P. vulgaris) and terrace systems on two slope classes. Two study plots were established on a steep gradient (25–40%) and a very steep gradient (>40%). The results showed an annual increase in the average diameter and height of N. cadamba of 1.78 cm and 1.84 m, respectively on the steep slope, and 1.68 cm and 1.53 m, respectively on the very steep slope. The surface run off and erosion rate were lower on the steep ground compared to the very steep ground. Erosion hazard indices and levels on the plots in the steep slope and very steep slope were categorized as low and very low; meanwhile the erosion hazard class was I. The profit of P. vulgaris cultivation was IDR 9,360,000.00 ha–1 per cropping season on steep slope and IDR 6,480,000.00 ha–1 per cropping season on very steep slope. The planting of P. vulgaris as an intercropping plant to fill empty land in between N. cadamba can increase the economic value obtained from selling P. vulgaris in the short term until the leaves of the N. cadamba plant are linked. The combination of planting N. cadamba–P. vulgaris and terrace system on steep slopes is therefore more profitable not only from the economic perspective, but also in lowering runoff and potential erosion rates than on very steep lands.